FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Ferra Charolina, 09.05.52.0005; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2012)
This study aims to determine the factors that affect audit delay in financial companies listed on the Indonesia Stock Exchange (IDX). Population in this study is a financial services company went public on the Stock Exchange of 2007-2010 with a sample of 192 companies. Dependent variable while the independent variable firm size, debt to equity ratio (debt ratio), profitability, and quality auditing the auditors opinion (KAP size).The results partially (t test) found that (1) firm size is not significant to the audit perpengaruh delay, (2) debt to equity ratio significantly influence the audit delay, (3) a significant effect on the profitability of audit delay, (4) audit opinion no significant effect on audit delay, (5) the quality of the audit no significant effect on audit delay. Simultaneously (F test) significance level of 0.000 means that the size of the company, debt to equity ratio, profitability, audit opinion and audit quality jointly influence sigifikan the audit delay. Suggestions for future research to consider other variables not examined in this study, and to extend the period of study so that it can be generalized.Keywords: Audit Delay, Company Size, Debt to Equity Ratio, Profitability, Opinion Auditor, Audit Quality.